2002
DOI: 10.1007/s00134-002-1237-2
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric adjustment following meningococcal disease treated on a PICU

Abstract: A significant proportion of children surviving meningococcal disease and their parents are likely to suffer psychological stress symptoms to a degree that warrants attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
53
0
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 8 publications
3
53
0
4
Order By: Relevance
“…Findings suggest that symptoms of posttraumatic stress disorder (PTSD) in parents and children are raised and that a significant number might experience distress to a degree where intervention would be beneficial [13,14].…”
Section: Introductionmentioning
confidence: 98%
“…Findings suggest that symptoms of posttraumatic stress disorder (PTSD) in parents and children are raised and that a significant number might experience distress to a degree where intervention would be beneficial [13,14].…”
Section: Introductionmentioning
confidence: 98%
“…Few studies have reported short-term and long-term prevalences of adverse consequences (such as physical and neuropsychological impairments) and health-related quality of life (HR-QoL) (2)(3)(4)(5)(6). These studies are limited, however, in that they do not differentiate as to severity of disease; the study populations included patients with sepsis, septic shock, or meningitis.…”
mentioning
confidence: 97%
“…Data on incidences of adverse consequences of meningococcal septic shock (such as physical and neuropsychological impairments) are rare [2][3][4].…”
mentioning
confidence: 99%